Perkembangan Sosial Emosional Anak Usia Dini 2-4 Tahun pada Keluarga Dengan Pola Asuh Permisif di Desa Papar Kecamatan Papar Kabupaten Kediri - Safitri, Amelia; Roesminingsih, MV. (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
Parenting is a parenting style used by parents in educating, guiding, and raising children. There are three types of parenting styles, namely authoritarian, democratic, and permissive parenting styles. In this study, researchers focused on permissive parenting on the social emotional developments of early 2-4 year old children in Papar Village, Papar Subdistrict, Kediri Regency. This study used a qualitative descriptive approach. Data collection was carried out using interviews, observation, and documentation. Then the data were analyzed using data collection, data condensation, data presentation, verification and conclusions. The result show that the application of permissive parenting that occurs causes social emotional development of children aged 2-4 years resulting in unfavorable childrens attitudes including aggressiveness, disobedience, behaving as they please.